CASE LAW OF THE COURT OF JUSTICE OF EUROPEAN UNION: A VISIT TO THE WINE CELLAR - Alina Mihaela CONEA (Challenges of the Knowledge Society)
`It must be observed that a quality wine is a very specific product. Its particular qualities and characteristics, which result from a combination of natural and human factors, are linked to its geographical area of origin and vigilance must be exercised and efforts made in order for them to be maintained. (Court of Justice of European Union, Rioja Wine Judgement)`1 The present paper will consider some of the most relevant judgements of the Court of Justice of European Union regarding wine. Coincidentally or not many of this cases are also landmark decisions of the European Union law. The purpose of this paper is to present the variety of European Union law areas enriched through the Court wine judgments: intellectual property, free movement of goods, fiscal barrier to trade, EU legal order, fundamental rights, public health and external relations. Surveying the wine jurisprudence of the Court of Justice of European Union resembles a wine testing. One can sense the savours rich bouquet that the case law express, on strong cultural choices, policies, lifestyle or identity at national and European level.